Influence of the background, substrate and thickness in light behaviour and colour of zirconia-reinforced lithium silicate (ZLS) glass-ceramic - Dos Santos, Ana Rita Canhão Rebelo (2021)
Objective: To evaluate the influence of background, substrates and thickness on the color and light behaviour of two ZLS glass ceramics. Material and Methods: Standardized disc-shape specimens (12 x 1.2 mm), color A1 HT, of Celtra Duo and Vita Suprinity (n=30), were tested over a white/black background, and divided in five groups (n=6) to be tested over five substrates (polished gold alloy, white zirconia and composite, dentine and enamel A1 colour). The L*, C*, h*, a*, b* and ΔE values, were recorded in two thicknesses (1.2 and 2.4 mm). Translucency parameter (TP), contrast ratio (CR) and opalescence parameter (OP) were calculated. Data was analysed with non-parametric tests: Mann Whitney between ceramic materials for thickness, Wilcoxon for thicknesses in substrates and ceramic material and Kruskal-Wallis with Bonferroni corrections tests (p<0,01) for substrates. Results: For 2.4 mm, the ΔE values were always higher independently of ceramic material or substrates. Vita Suprinity registered lower values than Celtra Duo. Zirconia substrate registered the lower values. For 1.2 mm, dentine registered the lower values. Gold alloy and composite substrates registered the lower ΔE values for 1.2 mm Celtra Duo and 2.4 mm Vita Suprinity specimens. CT and OP higher values and TP lower values were registered for 2.4 mm Vita Suprinity. It was impossible to calculate for Celtra Duo specimens. Conclusions: Background, substrate and thickness had significant influence in light behaviour and final color of ZLS glass ceramics. Substrates Gold alloy and dentine exhibited clinical acceptable ΔE values for 1.2 mm Celtra Duo specimens.